Political risk, institutions and foreign direct investment: How do they relate in various European countries? - Vladimír Benáček; Helena Lenihan; Bernadette Andreosso-O'Callaghan; Eva Michalíková; Denis Kan (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper examines theoretically and empirically the extent to which the decision by foreign firms to invest in a group of countries is influenced by economic factors, as opposed to political risk and institutional performance. We consider the importance of these factors as drivers of foreign direct investment (FDI) for 32 European countries (subsequently divided into three pooled clusters) by means of panel regression techniques in two specifications over the 1995-2008 period. Our results suggest that risk and institutional factors considered in both static and dynamic perspectives significantly influence the behaviour of investors. Policies and institutions that vary widely between countries modify their decision-making, so that the purely economic factors have different statistical significance and impacts on the intensity of FDI, as was revealed by clustering countries into three groups according to levels of economic maturity. Additionally, not all factors of risk have an identical impact on FDI decisions in particular groups of countries. However, we find that as measures of political risk, monetary discipline, low regulation, effective government and good education prove to be highly significant for most country groupings. All of these measures reduce political risk and positively affect the level of FDI.
Keywords: F2; D81; C23; 330; FDI; Political risk; Economic institutions; Panel regression; European Union